Primula centellifolia (Primulaceae), a new species from south-central China - Xu, Yuan; Hu, Chi-Ming; Hao, Gang (Phytotaxa, 2017)
A new species of Primulaceae, Primula centellifolia G.Hao, C.M.Hu & Y.Xu, from Sichuan and Guizhou, China, is described and illustrated. From general morphology it is allied to the species of P. sect. Monocarpicae, and superficially resembles P. scopulicola, but can be distinguished by its much smaller statue, slender scape and calyx with linear lanceolate and obtuse lobes.